Evaluating the Role of Vitamin D Supplementation in Enhancing Muscle Strength Among Athletes - Wulandari, Ni Komang Ayu; Radhana, Putu Sukma (PT BMW Journal Sejahtera, 2025)
Background: Vitamin D is essential for musculoskeletal health, and a deficiency can affect muscle performance. Athletes, especially those training indoors or in areas with limited sunlight, may lack sufficient vitamin D. Aim: This review examines how vitamin D supplements affect muscle strength in athletes across different sports. Methods: A comprehensive literature search was conducted across PubMed, Scopus, and Science Direct for randomized controlled trials (RCTs) published between 2014-2024. Studies examining vitamin D supplementation in athletes and its impact on muscle strength outcomes were included. Data on dosage, duration, baseline vitamin D levels, and muscle strength assessments were extracted and analyzed. Results: Four RCTs were identified, with supplementation doses from 600 IU to 5000 IU daily. The results indicate that vitamin D supplements significantly improve lower limb strength, power, and recovery in athletes with initial vitamin D insufficiency (levels below 30 ng/mL). For athletes with sufficient vitamin D levels, supplements had little to no impact. Factors such as the length of the intervention and initial vitamin D levels were important in determining the outcomes. Conclusion: Vitamin D supplements can benefit athletes with a deficiency, enhancing muscle strength. However, they show limited effects on those with adequate vitamin D. Future research should focus on determining the ideal dosing and examining the long-term impact of supplements on athletic performance.